O processo de construção curricular e práticas pedagógicas nas narrativas docentes: a rede Municipal de Educação de Santo André/SP (1998 – 2018) - Cavalcanti, Marco Alexandre Nonato (2020)
This thesis aims to record and analyze the curricular reforms in the Education Secretariat of the Municipality of Santo André, from 1998 to 2018. It also intends to understand how the teachers of the municipal network of Santo André articulated the conditions of teaching work and their professionalization with the proposals placed by the curricular reforms of the municipality, in the socioeconomic context in which we currently live. It is also interested in verifying how these curricular reforms interfered, positively or negatively, in the autonomy and professionalization of teachers. He considers it relevant that the professionals involved reconstitute / recover their condition as producers of knowledge, with which they work or have worked, in order to resize their place as subjects of educational action. We start from the hypothesis that the teaching participation in the curricular discussions positively leverages the pedagogical practice and its professional identity. Using thematic oral history as a methodology, it analyzes the narratives of four teachers, trained in Pedagogy, working in Elementary School I, in two public municipal schools. The interviews showed that the teachers' professional knowledge is linked to their context and reflect relationships of teaching identity and professionalization. This research supports the social construction of the curriculum according to Goodson (2001); the concepts of Julia (2001) e Viñao-Frago (2000) for discussions about school culture; Tardif (2002) for the debate on professionalization and teacher identity. The reflections on thematic oral history and memory are based on the work of Alberti (1997), Halbwachs (1990), Le Goff (2003), Meihy (2005), Pollak, (1992), and Walter Benjamin (1994)